2023
DOI: 10.3389/fcell.2023.1164166
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ERK signaling pathway in promoting angiogenesis for treating ischemic diseases

Abstract: The main treatment strategy for ischemic diseases caused by conditions such as poor blood vessel formation or abnormal blood vessels involves repairing vascular damage and encouraging angiogenesis. One of the mitogen-activated protein kinase (MAPK) signaling pathways, the extracellular signal-regulated kinase (ERK) pathway, is followed by a tertiary enzymatic cascade of MAPKs that promotes angiogenesis, cell growth, and proliferation through a phosphorylation response. The mechanism by which ERK alleviates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Additionally, previous studies have highlighted the critical role of p-ERK in regulating endothelial migration and proliferation, which is essential for angiogenesis. Song et al (2023). In our current study, we employed SCH772984 to demonstrate that shear stress-mediated ERK/MAPK signaling participates in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have highlighted the critical role of p-ERK in regulating endothelial migration and proliferation, which is essential for angiogenesis. Song et al (2023). In our current study, we employed SCH772984 to demonstrate that shear stress-mediated ERK/MAPK signaling participates in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK can increase the production of VEGF and enhance its binding to its receptor, VEGFR, thus amplifying the angiogenic signals. [46] In their study, Gong et al, [10] also found that ononin could suppress HIF-1α expression after 48 h of incubation. [10] Also, evidence from traditional Chinese medicines hints towards the potential inhibitory effect of ononin on HIF-1α.…”
Section: Antiangiogenic Action Of Ononinmentioning
confidence: 91%
“…This activation leads to ECM breakdown, facilitating angiogenesis [53]. Additionally, VEGF induces a survival mechanism in ECs and promotes their migration and proliferation through MAPK/ERK and PI3K/Akt pathways [3,54]. PlGF, a member of the VEGF family, has a controversial role in tumor angiogenesis, with reports suggesting both proangiogenic and antiangiogenic properties.…”
Section: Possible Molecular Mechanisms Of Tumor Angiogenesis: Angioge...mentioning
confidence: 99%